Predictors of Utilisation of Skilled Maternal Healthcare in Lilongwe District, Malawi - Kazanga, Isabel; Munthali, Alister C; McVeigh, Joanne; Mannan, Hasheem; MacLachlan, Malcolm (International journal of health policy and management, 2019)
BACKGROUND: Despite numerous efforts to improve maternal and child health in Malawi, maternal and newborn mortality rates remain very high, with the country having one of the highest maternal mortality ratios globally. The aim of this study was to identify which individual factors best predict utilisation of skilled maternal healthcare in a sample of women residing in Lilongwe district of Malawi. Identifying which of these factors play a significant role in determining utilisation of skilled maternal healthcare is required to inform policies and programming in the interest of achieving increased utilisation of skilled maternal healthcare in Malawi. METHODS: This study used secondary data from the Woman's Questionnaire of the 2010 Malawi Demographic and Health Survey (MDHS). Data was analysed from 1126 women aged between 15 and 49 living in Lilongwe. Multivariate logistic regression was conducted to determine significant predictors of maternal healthcare utilisation. RESULTS: Women's residence (P=.006), education (P=.004), and wealth (P=.018) were significant predictors of utilisation of maternal healthcare provided by a skilled attendant. Urban women were less likely (odds ratio [OR] = 0.47, P=.006, 95% CI = 0.28-0.81) to utilise a continuum of maternal healthcare from a skilled health attendant compared to rural women. Similarly, women with less education (OR = 0.32, P=.001, 95% CI = 0.16-0.64), and poor women (OR = 0.50, P=.04, 95% CI = 0.26-0.97) were less likely to use a continuum of maternal healthcare from a skilled health attendant. CONCLUSION: Policies and programmes should aim to increase utilisation of skilled maternal healthcare for women with less education and low-income status. Specifically, emphasis should be placed on promoting education and economic empowerment initiatives, and creating awareness about use of maternal healthcare services among girls, women and their respective communities.
Keywords: služby zdravotní péče o dítě; pacientův souhlas se zdravotní péčí; Health Services Accessibility; kojenec; Middle Aged; průzkumy a dotazníky; předpověď; Patient Acceptance of Health Care; dostupnost zdravotnických služeb; Infant; Adult; dítě; Child; Infant, Newborn; logistické modely; Child, Preschool; Forecasting; ženské pohlaví; novorozenec; Humans; předškolní dítě; Mothers; matky; Surveys and Questionnaires; odds ratio; lidé středního věku; Maternal Health Services; Logistic Models; Child Health Services; dospělí; Female; Malawi; služby zdravotní péče o matku; Health System; lidé; Maternal Healthcare; Odds Ratio